Controlling spółek z kapitałowym udziałem gminy - Bednarek, Piotr (Controllership of local government's subsidiary companies, 2006)
This article deals with a problem of using controllership as a support of corporate governance in a special capital group consisted of local government and its subsidiary companies. Firstly, there are main premises of increasing role of corporate governance and using controllership in local government presented. Next, the definition of controllership of local government’s subsidiary companies from the point of view of holding entity is formulated. Finally, tasks and instruments of the controllership are proposed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 28-36